Worldview and mind: religious thought and psychological development - Webb, Eugene (Eric Voegelin Institute in Political Philosophy, 2009)
Intro -- Contents -- Acknowledgments -- Introduction: The Power of Worldviews -- 1. The Idea of a Psychology of Worldviews -- 2. Jean Piaget and Bernard Lonergan -- 3. From Psychological Stages to Orders of Consciousness -- 4. Death Anxiety and Symbols of Immortality -- 5. Mimetic Theory -- 6. From Psychology to Theology -- 7. The Dynamic Diversity of Religious Worldviews -- 8. Religion and Personhood -- 9. Dialogical Faith -- Conclusion: The Future of Religion -- Bibliography -- Index.